IITA’s social science and agribusiness research for development: compendium of research highlights 1967–2022 - Manyong, V.; Feleke, S.; Abdoulaye, T. (International Institute of Tropical Agriculture, 2023)
Background The social science and agribusiness research program at the International Institute of Tropical Agriculture (IITA) has supported the Institute’s research and delivery efforts since 1967. This Compendium highlights the main achievements of IITA’s social science and agribusiness research over the 55 years from 1967 to 2022. Methodology The Compendium is a product of a systematic review conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines (Grant & Booth 2009), following the Search, Appraisal, Synthesis, and Analysis (SALSA) framework (Moher et al. 2010). This involved four stages: search (keyword identification and database search); appraisal (paper selection through the PRISMA statement); synthesis (data extraction and categorization); and analysis (data analysis, comparison of results, and conclusion). The online search for IITA’s social science and agribusiness research publications in the CGSpace repository of agricultural research outputs yielded 5,755 publications comprising 4,836 journal articles and 919 books and book chapters. Applying the screening and eligibility criteria based on the PRISMA guidelines finally resulted in 597 publications used for data synthesis (data extraction and categorization). Of the 597 documents reviewed, 584 were peer-reviewed journal articles, and 13 were book and book chapters. The synthesis was based on seven variables of interest. These include research themes; research crops; research methods; name of journal; year of publication; country of study; and research findings. The extracted data were then analyzed to assess the achievements of the 55 years of research efforts.